2013
DOI: 10.3109/0886022x.2013.774672
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Angle of Needle Entry for Internal Jugular Vein Catheterization with a Neutral Head Position: A CT Study

Abstract: Purpose: The aim of this study is to determine the optimal angle of needle entry in the sagittal plane for internal jugular vein (IJV) catheterization with the central approach while the head is in the neutral position. Methods: The contrast-enhanced carotid artery computed tomography angiographies of 123 consecutive patients were retrospectively reviewed. The point of merger between the sternal and clavicular heads of the sternocleidomastoid muscle was assumed as a clinical entry (CE) point. The angle between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, the IJV catheterisation in neutral head position is sometimes impossible in infants because of the big head and the relatively short neck. Moreover, the location of the IJV in neutral head position would be different compared with applying the head rotation to the contralateral side, in anatomical landmark and the needle entry points . Furthermore, the success rate in the neutral head position was significantly lower than that in the 45° head rotation (57.5% vs. 97.5%) .…”
Section: Discussionmentioning
confidence: 95%
“…However, the IJV catheterisation in neutral head position is sometimes impossible in infants because of the big head and the relatively short neck. Moreover, the location of the IJV in neutral head position would be different compared with applying the head rotation to the contralateral side, in anatomical landmark and the needle entry points . Furthermore, the success rate in the neutral head position was significantly lower than that in the 45° head rotation (57.5% vs. 97.5%) .…”
Section: Discussionmentioning
confidence: 95%
“…Head rotation can increase the visibility of anatomical landmarks, thus facilitating skin puncture and cannulation. 3,12,18 However, Lamperti et al 12 reported that the perception of difficulty in patients in the neutral and head turned positions during IJV cannulation did not significantly differ among the anesthesiologists (9% in the neutral position vs. 11% in the head turned position) when performed under ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to avoid CA puncture during the IJV cannulation in dialysis patients, 18 which can occur even when performed under ultrasound guidance. Head rotation can increase the visibility of anatomical landmarks, thus facilitating skin puncture and cannulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of 123 consecutive patients who had a CT, the right internal jugular (RIJ) had an average diameter of 15.6 mm versus 11.7 left internal jugular, the overlap with the carotid artery was not significantly different comparing right to left, and depth of the skin to vein was also similar (Ozbek et al 2013). The authors also examine the incidence of veins less than 7 mm, which was 4.4% for RIJs and 21.9% for left internal jugular veins.…”
Section: Internal Jugularmentioning
confidence: 99%